The relationships and configuration of universal and optional healthcare financing schemes in Czechia - Jan Mertl (DANUBE: Law, Economics and Social Issues Review, 2018)
In developed countries, both universal and optional parts of healthcare exist. This article shows the importance and fiscal position of universally available care and suggests where it can be extended by optional financing schemes such as prepaid health programmes. We use a comparative approach, SWOT analysis and synthesis of individual mechanisms of health financing into a single health system. A simple scheme of possible health system financing configuration is created, and we classify the financial resources and schemes used accordingly. Overall this article introduces a theoretically substantiated overview of health policy options for Czechia based on principles of universally available care, solidarity, fiscal neutrality, adequate fiscal space for health and voluntary private health expenditure.
Keywords: 330; Health System; Health Insurance; Earmarked Taxation; Prepaid Health Programmes; Solidarity